Wars in Review: Subaltern Methodologies in Conflict Studies - Yadav, Rishika (Millennium, 2021)
This essay reviews four disparate studies on war narratives: ‘Right to Mourn’ by Suhi Choi (2019), ‘Fly Until You Die’ by Chia Youyee Vang (2019), ‘Soldiers in Revolt’ by Maggie Dwyer (2018), ‘Breaking the Binaries in Security Studies’ by Ayelet Harel-Shalev and Shir Daphna-Tekoah (2019). The studies take a ‘view-from-below’ approach and build new theoretical frameworks that not only expose ‘the price of war’, but also investigate how ‘subaltern subjects’ subjects view their place and participation in the conflict and resist over-arching homogenous interpretations. The studies respectively focus on post-war remembrance in South Korea, oral histories of Hmong pilots, mutinying in West African states, and the experiences of female combatants in the Israeli Defence Forces. Although dissimilar in terms of geographic spaces, actors and even methodology, the authors all commonly challenge established binaries within conflict studies that assume a separation of the ‘military’ and the ‘civilian’, the prevalence of power-hierarchies within armed forces, and the supposed passiveness of powerless actors in conflict. This essay reviews these books as not individual publications that contribute to the literature of their own disciplines, but as interactive theoretical frameworks that not only dispute prevailing theories of war but also present new understandings on how these narratives interrelate.